Environmental life cycle assessment, uncertainty, and sensitivity analysis of hydrogen production from biomass gasification with various agents - Guler, Nurhan Uregen; Yumurtaci, Zehra (ELSEVIER, 2025)
In this study, a comprehensive environmental analysis was conducted on three gasification scenarios based on gasifying agents (steam, oxygen and air). An environmental life cycle assessment (LCA) was performed for cradle-to-gate analysis to produce 1 kg of hydrogen as functional unit (FU). Using SimaPro LCA software, fifteen environmental impact categories were analyzed and compared for gasification scenarios according to ReCiPe 2016 Midpoint and three damage assessment categories were analyzed based on ReCiPe 2016 Endpoint methods. Steam gasification is the most environmentally friendly way of hydrogen production among the processes studied. The Global Warming Potential (GWP) values with the largest effect among the impact categories are 7.78, 11.63 and 12.95 kg CO2-eq/kg H2 for steam, oxygen and air gasification processes, respectively. Monte Carlo simulation (MCS) was performed to assess data uncertainty while sensitivity analysis was employed to identify process hotspots on environmental impacts. The uncertainty analysis based on 10,000 MCS iterations showed low variability with coefficient of variation (CV) remaining below 5 % in all gasification scenarios. The standard error of the mean (SEM) values for steam, oxygen, and air gasification were 0.0037, 0.00564, and 0.00492, respectively. These findings provide environmentally friendly and sustainable strategies for hydrogen production from biomass gasification.
Keywords: Biomass Gasification; Hydrogen production; Life cycle assessment; Uncertainty analysis; Sensitivity analysis; Simapro; STEAM GASIFICATION; PERFORMANCE; ADJUSTMENT; COMBUSTION; SYNGAS; CARBON; Engineering